PENGARUH TEKNIK PIJAT OKSITOSIN TERHADAP PENURUNAN NYERI PERSALINAN : EVIDENCE BASED CASE REPORT (EBCR) (Politeknik Kesehatan Kemenkes Bandung, 2022)
Background: Labor pain is a factor that can cause discomfort and anxiety. This can result in weak uterine contractions so that prolonged labor will occur. One effort to deal with labor pain can be done with pharmacological and non-pharmacological methods. One of the non-pharmacological methods is by using oxytocin massage. Purpose: This evidence-based case report aims to determine whether oxytocin massage can reduce labor pain in the first stage of labor at the Pacet Health Center, Bandung Regency. Method: Search for articles about the effectiveness of oxytocin massage in labor mothers was conducted on Garuda and Google Scholar. The keywords used were